2013
DOI: 10.1371/journal.pone.0067032
|View full text |Cite
|
Sign up to set email alerts
|

Dynein Light Chain 1 (DYNLT1) Interacts with Normal and Oncogenic Nucleoporins

Abstract: The chimeric oncoprotein NUP98-HOXA9 results from the t(7;11)(p15;p15) chromosomal translocation and is associated with acute myeloid leukemia. It causes aberrant gene regulation and leukemic transformation through mechanisms that are not fully understood. NUP98-HOXA9 consists of an N-terminal portion of the nucleoporin NUP98 that contains many FG repeats fused to the DNA-binding homeodomain of HOXA9. We used a Cytotrap yeast two-hybrid assay to identify proteins that interact with NUP98-HOXA9. We identified D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 75 publications
1
3
0
Order By: Relevance
“…DYNLT3 protein has been reported to form the light chain component of the cytoplasmic dynein motor protein complex [33,34]. Its paralog, DYNLT1, has been found to promote tumor progression [35][36][37]. Thus, our current study and the published studies indicate that cytoplasmic dynein motor proteins play a critical role in tumor progression.…”
Section: Discussionsupporting
confidence: 61%
“…DYNLT3 protein has been reported to form the light chain component of the cytoplasmic dynein motor protein complex [33,34]. Its paralog, DYNLT1, has been found to promote tumor progression [35][36][37]. Thus, our current study and the published studies indicate that cytoplasmic dynein motor proteins play a critical role in tumor progression.…”
Section: Discussionsupporting
confidence: 61%
“…Additional studies have focused on the correlation between DYNLT1 and cancer. Sarma et al14 found that DYNLT1 interacted with nucleopore proteins, which play a role in the dysregulation of gene expression and the proliferation of hematopoietic cells. Cervantes et al15 revealed that the DYNLT1 exhibited significantly increased expression in liver cancer and participated in the progression of liver cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Although still debated, the aberrant localization and function of the chimeras, as well as their interaction with endogenous Nup98, appear to contribute to leukemogenesis (reviewed in Gough et al. , 2011 ; Franks and Hetzer, 2013 ; see also Sarma and Yaseen, 2013 ; Salsi et al. , 2014 ).…”
Section: Introductionmentioning
confidence: 99%